Isolation and Characterization of Nanocellulose Obtained from Industrial Crop Waste Resources by Using Mild Acid Hydrolysis - Moreno, Galia (2018)
Cellulose, microcrystalline cellulose and nanocellulose were prepared from three agricultural waste resources: pineapple leaf (PALF), banana rachis (BR), and sugarcane bagasse (SCB). Each waste resource was first converted into microcrystalline cellulose which was subsequently converted into cellulose nanoparticles by using mild (30% w/v) and strong (60% w/v) sulfuric acid concentrations for extraction. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA) were used to characterize each waste resource and extracted cellulosic materials. Furthermore, nanocelluloses were studied by zeta potential, size analysis, and transmission electron microscopy (TEM). Cellulose nanowhiskers were successfully obtained and isolated with a 33% average yield by applying a mild acid treatment. Substrates BR and SCB proved to be more promising agricultural waste resources in terms of their crystalline cellulosic content and properties.